Pengaruh Terapi Musik Klasik (Mozart) Terhadap Kemampuan Berbahasa Pada Anak Autisme di SLBN Prof.Sri.Soedewi.Masjchun Sofwan,S.H Kota Jambi - Ananda, Fenni Dwi; Nasution, Riska Amalya; Yuliana, Yuliana (Jurnal Ners, 2023)
The prevalence of children with autism in Indonesia has reached 2.4 million in a few years. Children with autism have difficulties in growth and development, especially in language skills. Language ability is an important aspect that must be owned by everyone. There are various methods to assist in developing language skills, one of which is classical music therapy (Mozart). This study aims to determine the effect of classical music therapy (Mozart) on the language skills of children with autism at the SLBN Prof. Dr. Sri Soedewi Masjchun Sofwan, S.H. Jambi. This study uses a quantitative research type with a pre-experimental research design (pre-post test design with one group). The number of samples in this study was 10 respondents with a total sampling technique. Statistical test using paired-sample t-test. Results of statistical tests using Shapiro-Wilk, obtained p-value = 0.05 > ? 5%. There was an effect of giving classical music therapy (Mozart) where at the time of the pretest, it was found that the most respondents’ language abilities were in the less category and after the post-test, the most respondents’ language abilities were in the good category. There is a significant influence between giving classical music therapy (Mozart) on language skills in children with autism. It is hoped that parents or teachers can provide music therapy as an adjunct in fostering children with autism to improve language skills.